2015
DOI: 10.5194/isprsarchives-xl-3-w3-335-2015
|View full text |Cite
|
Sign up to set email alerts
|

Uav-Based Acquisition of 3d Point Cloud – A Comparison of a Low-Cost Laser Scanner and SFM-Tools

Abstract: ABSTRACT:The Project ADFEX (Adaptive Federative 3D Exploration of Multi Robot System) pursues the goal to develop a time-and cost-efficient system for exploration and monitoring task of unknown areas or buildings. A fleet of unmanned aerial vehicles equipped with appropriate sensors (laser scanner, RGB camera, near infrared camera, thermal camera) were designed and built. A typical operational scenario may include the exploration of the object or area of investigation by an UAV equipped with a laser scanning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Studies on the horizontal and vertical accuracy of the SfM-derived model report differing results. Mader et al [24] reported an RMS value of 0.049 m when comparing SfM-derived points to TLS results during monitoring of a bridge. Hrůza et al [25] inspected damage of a forest hauling road and reported an altitudinal RMSE of 0.020 m and a positional RMSE of 0.012 m, while the flight altitude was 4-6 m above the surface of the road.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the horizontal and vertical accuracy of the SfM-derived model report differing results. Mader et al [24] reported an RMS value of 0.049 m when comparing SfM-derived points to TLS results during monitoring of a bridge. Hrůza et al [25] inspected damage of a forest hauling road and reported an altitudinal RMSE of 0.020 m and a positional RMSE of 0.012 m, while the flight altitude was 4-6 m above the surface of the road.…”
Section: Discussionmentioning
confidence: 99%
“…RGB or NIR (near infrared) cameras are used in the majority of these studies. Many other applications of UAVs have also been described apart from forestry, e.g., agriculture [22,23], damage detection of buildings [24,25], landslide research [26], research of…”
Section: Introductionmentioning
confidence: 99%
“…The laserscanner has a small size of 62mm × 62mm × 87.5mm and a weight of 210g. Therefore and because of its low cost, it is frequently applied to UAS's (Huh et al, 2013;Mader et al, 2015). Table 1 summarizes the specifications of all sensors used in our experiments.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…However, there is evidence that interest in combining multiple high‐resolution datasets obtained from both terrestrial, airborne, and surface systems is growing. Examples include combining aerial imagery from UAV platforms with ALS (Legleiter, ) and MLS (Flener et al, ), bathymetric ALS and ULS (Mandlburger et al, ), airborne imagery and ALS (Rapple et al, ), and multiple UAV flights with imagery and laser configurations (Mader et al, ). This has enabled researchers to improve their modelling of combined subaerial and subsurface morphology, better understand riparian vegetation encroachment, and enhance current data integration approaches; all of which would be more challenging through single dataset analysis.…”
Section: The State Of the Artmentioning
confidence: 99%